Regioselective addition of Ti enolates to conjugated enones: New insights into the mechanism based on experimental and DFT investigation. Issue 23 (7th June 2018) - Wu, Chenggui; Mao, Shanjian; Deng, Guisheng; Qiu, Yongge
Abstract: The regioselective addition mechanism of the Ti(IV) enolates derived from α-diazo-β-keto carbonyl compounds and α-diazo-β-keto phosphonates to conjugated enones has been studied on the basis of a hypothetical bridging chloride-controlled theory, by density functional theory (DFT), and experimentally. The DFT results indicate that, for the Ti(IV) enolate3 derived from α-diazo-β-keto carbonyl compounds, the free energy of the bridging chloride-controlled 1, 2-addition transition state is 2.4 kcal/mol higher than that of 1, 4-addition, and the calculated enthalpies of 1, 2-addition is 4.36 kcal/mol more than that of 1, 4-addition. For the Ti(IV) enolate4 derived from α-diazo-β-keto phosphonates, in contrary, the free energy of the bridging chloride-controlled 1, 2-addition transition state is 1.1 kcal/mol lower than that of 1, 4-addition, and the calculated enthalpy of 1, 2-addition is 3.46 kcal/mol less than that of 1, 4-addition. Our findings demonstrate that the nucleophilic addition of these Ti(IV) enolates to conjugated enones was carried out not only kinetically but also irreversibly for the first time. Graphical abstract: